Direito de construir - Meirelles, Hely Lopes, 1917-1990.; Dallari, Adilson Abreu, 1941.; Di Sarno, Daniela Libório.; Novis, Mariana.; Wagner Junior, Luiz Guilherme da Costa. (São Paulo : Malheiros, 2011)
Inclui bibliografia